TREND ANALYSIS OF COCOA COMMODITY PRICES IN SOUTH SULAWESI PROVINCE - Sjamsir, Zulkifli -; ,, Sumarni; Jopi, Hafikah Durmiati; R, Suhartina (Universitas Muhammadiyah Makassar, 2022)
This study aims to analyze the trend of cocoa commodity prices in South Sulawesi Province.The data sources used are data obtained from the BPS (Central Bureau of Statistics) of South Sulawesi Province. This study uses secondary data (time series) from 2011-2020, the research method used in this study is a quantitative method. Analysis of the data used in this study is linear regression with the least square method (least square method).The results of this study indicate that the trend of cocoa commodity prices in South Sulawesi Province in the period from 2011 to 2020 shows the development of cocoa prices every year on average of Rp. 13,078.00 per kilo gram. Keywords: Trend, Price, Cocoa